2014
DOI: 10.1111/bph.12431
|View full text |Cite
|
Sign up to set email alerts
|

Cell death and the mitochondria: therapeutic targeting of the BCL‐2 family‐driven pathway

Abstract: The principal biological role of mitochondria is to supply energy to cells; although intriguingly, evolution has bestowed another essential function upon these cellular organelles: under physiological stress, mitochondria become the cornerstone of apoptotic cell death. Specifically, mitochondrial outer membrane permeabilization (MOMP) allows cell death factors such as cytochrome c to be released into the cytoplasm, thus inducing caspase activation and the eventual destruction of essential cellular components. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 145 publications
(193 reference statements)
5
106
0
2
Order By: Relevance
“…On the basis of this fact, programmed cell death inhibits tumor growth and constitutes potential target for cancer therapy. Of the three common types of programmed cell death, including apoptosis, autophagy and necrosis, apoptosis is the most extensively studied and well-defined one (35)(36)(37)(38). We have found that lycorine initiates apoptotic cell death in HCC cells, which is supported by the results of DAPI staining and V-FITC/PI double staining.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…On the basis of this fact, programmed cell death inhibits tumor growth and constitutes potential target for cancer therapy. Of the three common types of programmed cell death, including apoptosis, autophagy and necrosis, apoptosis is the most extensively studied and well-defined one (35)(36)(37)(38). We have found that lycorine initiates apoptotic cell death in HCC cells, which is supported by the results of DAPI staining and V-FITC/PI double staining.…”
Section: Discussionsupporting
confidence: 52%
“…Caspases that belong to the family of cysteine proteases are integral components of the apoptotic pathway. Recently, many studies have shown that a variety of chemotherapeutic agents promote apoptosis through the activation of caspases (38)(39)(40). In this study, we have found that lycorine treatment markedly augments caspase activity, and upregulates cleaved caspase-3 and PARP.…”
Section: Discussionsupporting
confidence: 52%
“…A number of drugs directed at inhibiting anti-apoptotic BCL-2 family proteins have been developed, with some showing great promise in clinical settings (Weyhenmeyer et al, 2012;Roy et al, 2014). Two strategies are recommended to block Bcl-2 and Bcl-xL, including I) application of Bcl-2 antisense, and II) application of small molecule inhibitors of the Bcl-2 family of proteins.…”
Section: Cont) Preclinical and Clinical Trials Of Therapeutic Agentsmentioning
confidence: 99%
“…7 The BH3-mimetic concept has prompted the design of numerous small BH3 peptides or organic molecules. 8,9 However, many of the generated compounds turned out to act through off-target mechanisms. Only a few of them were found to behave as authentic BH3 mimetics with the ability to bind prosurvival proteins with high affinity and to induce BAX/BAK-dependent apoptosis in malignant cells.…”
Section: Bh3 Mimeticsmentioning
confidence: 99%
“…Only a few of them were found to behave as authentic BH3 mimetics with the ability to bind prosurvival proteins with high affinity and to induce BAX/BAK-dependent apoptosis in malignant cells. 8,9 The prototype ABT-737 and its orally bioavailable derivative navitoclax (formerly, ABT-263) bind and antagonize BCL-2, BCL-XL, and BCL-W (so they are referred to as BAD-like BH3 mimetics). 10,11 Navitoclax has shown significant therapeutic activity in cancer patients but with a doselimiting thrombocytopenia because of inhibition of BCL-XL (that is a prosurvival factor for platelets).…”
Section: Bh3 Mimeticsmentioning
confidence: 99%